Synthesis, radiolabeling and preliminary in vivo evaluation of [ 18F]FE-PE2I, a new probe for the dopamine transporter - Schou, Magnus; Steiger, Carsten; Varrone, Andrea; Guilloteau, Denis; Halldin, Christer (Bioorganic & medicinal chemistry letters, 2009)
The synthesis, radiosynthesis and preliminary PET evaluation of [18F]6 ( K i = 17 nM) is reported. A new dopamine transporter (DAT) ligand, ( E)- N-(3-iodoprop-2-enyl)-2β-carbofluoroethoxy-3β-(4′-methyl-phenyl) nortropane (FE-PE2I, 6), derived from PE2I ( 1), was prepared and found to be a potent inhibitor of rodent DAT in vitro. Compound 6 was radiolabelled with fluorine-18 ( t 1/2 = 109.8 min) for PET studies in monkeys. In vivo PET measurements showed a regional distribution in brain that corresponds to the known distribution of DAT. This binding was specific, reversible and the kinetics of [ 18F] 6 binding in brain were faster than for its lead compound, [ 11C] 1. The possible presence of a hydroxymethyl-radiometabolite formed by oxidation in the 3β-benzylic position of [ 18F] 6 warrants further detailed evaluation of the metabolism of [ 18F] 6. [ 18F] 6 is a potential radioligand for imaging DATs in the human brain with PET.